2015
DOI: 10.3892/mmr.2015.3700
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids from Triticum aestivum inhibit adipogenesis in 3T3-L1 cells by upregulating the insig pathway

Abstract: Abstract. The present study aimed to compare the potential anti-adipogenic effects and underlying mechanisms of the luteolin, isoscoparin and isoorientin flavonoids, purified from Triticum aestivum sprout (TA) in 3T3-L1 cells. The cells were treated with different concentrations of flavonoids for 8 days and the lipid accumulation was assessed using Oil-Red-O staining. The expression levels of the transcription factors and the genes involved in adipogenesis in the cells were assessed by reverse transcription-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 24 publications
4
44
0
Order By: Relevance
“…Natural products are considered a safe approach in treating metabolic syndrome [1], and their therapeutic potential against obesity has been extensively reviewed [2][3][4]. Of interest is isoorientin, a C-glycosyl flavonoid, which is found in rooibos, among other plants, and which displays strong ameliorative effects on obesity-linked complications [5,6]. Isoorientin, also referred to as homoorientin, is a C-glucosyl flavone that was first isolated by Koeppen and colleagues in 1962 from Aspalathus linearis, a South African indigenous plant, which is widely consumed as herbal tea (rooibos) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Natural products are considered a safe approach in treating metabolic syndrome [1], and their therapeutic potential against obesity has been extensively reviewed [2][3][4]. Of interest is isoorientin, a C-glycosyl flavonoid, which is found in rooibos, among other plants, and which displays strong ameliorative effects on obesity-linked complications [5,6]. Isoorientin, also referred to as homoorientin, is a C-glucosyl flavone that was first isolated by Koeppen and colleagues in 1962 from Aspalathus linearis, a South African indigenous plant, which is widely consumed as herbal tea (rooibos) [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have indicated that extract of TA has antidiabetic, antihyperlipidemic, and anticancer effects [4][5][6][7][8][9]. Moreover, TA extract is known to contain several phytocompounds such as leuteolin, isoscoparin, isoorientin, and triticumoside [10][11][12]. However, there have not yet been any studies on the effects and potential mechanisms of anticancer effects of compounds isolated from TA, until now.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown phenolic compounds and vitamins synthesized during the sprouting of wheat grass have potent antioxidant and antiinflammatory properties (Benedetti et al, ; Luyen et al, ; Mohan et al, ). In addition, it was also reported recently that a constituent of wheatgrass has anti‐obesity effects (Im et al, ; Luyen et al, ; Poudel et al, ). Furthermore, polysaccharide isolated from wheatgrass was found to reduce blood glucose level in streptozotocin (STZ)‐induced diabetic mice (Mohan et al, ) and has a stimulatory effect on insulin response (Lee et al, ).…”
Section: Introductionmentioning
confidence: 79%
“…Previous studies have shown that the antioxidant and antiinflammatory properties of wheatgrass constituents are due to the inhibition of NF‐κB activation (Poudel et al, ; Lee et al, ). Several studies have described the anti‐obesity and anti‐diabetic effects of wheatgrass (Luyen et al, ; Lee et al, ).…”
Section: Discussionmentioning
confidence: 99%